2014
DOI: 10.1128/mcb.00246-14
|View full text |Cite
|
Sign up to set email alerts
|

Autoactivation of the MDM2 E3 Ligase by Intramolecular Interaction

Abstract: The RING domain ubiquitin E3 ligase MDM2 is a key regulator of p53 degradation and a mediator of signals that stabilize p53. The current understanding of the mechanisms by which MDM2 posttranslational modifications and protein binding cause p53 stabilization remains incomplete. Here we present evidence that the MDM2 central acidic region is critical for activating RING domain E3 ligase activity. A 30-amino-acid minimal region of the acidic domain binds to the RING domain through intramolecular interactions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 62 publications
3
29
0
Order By: Relevance
“…Our analysis also detected a previously unidentified AD-RING internal binding in MDMX. We recently showed that the AD-RING internal interaction in MDM2 activates the ubiquitin E3 ligase activity of the RING domain (20). Here we found that in MDMX, the AD-RING binding is involved in suppressing nuclear translocation, presumably by concealing the NLS in the RING domain (16).…”
Section: Discussionmentioning
confidence: 61%
“…Our analysis also detected a previously unidentified AD-RING internal binding in MDMX. We recently showed that the AD-RING internal interaction in MDM2 activates the ubiquitin E3 ligase activity of the RING domain (20). Here we found that in MDMX, the AD-RING binding is involved in suppressing nuclear translocation, presumably by concealing the NLS in the RING domain (16).…”
Section: Discussionmentioning
confidence: 61%
“…Recently, Cheng et al shown that the HDM2 RING domain is activated by intramolecular interaction with its acidic domain (40); thus, we hypothesized that the acidic domain in the construct HDM2(1-301) is able to recognize the RING domain of HDMX, since both RING domains have sequences with greater than 75% similarity (41) (Fig. 4g).…”
Section: Resultsmentioning
confidence: 96%
“…The E2-E3 pair could play a role in substrate specificity under different cellular conditions. Another question that arises from this work is the role of intramolecular interactions that has recently been described for HDMX (45,46) and for HDM2 (40). These intramolecular interactions could add another level of regulation to the way the domains are exposed to the solvent to allow highly accurate control of the interactome of HDM2.…”
Section: Discussionmentioning
confidence: 96%
“…3F). Biologically, the acidic domain is a core domain for the intramolecular binding between the acidic and RING domains, which also mediates the interaction with HAUSP (19, 20). Because the KQKQ-MDM2 mutant bound HAUSP more strongly than did the wild-type MDM2 (Fig.…”
Section: Resultsmentioning
confidence: 99%